MANAGEMENT OF RISK FACTORS FOR PRE-ECLAMPSIA - Anita, Anita; Aprina, Aprina; Astuti, Titi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Globally, preeclampsia is still a problem, 10% of pregnant women throughout the world experience preeclampsia, and it is the cause of 76,000 maternal deaths and 500,000 infant deaths every year. Lampung Province is a province where the number of maternal deaths is still quite high, the latest IDHS data in 2018 shows The highest MMR was 818 people (87.99/100,000 KH) in Tanggamus Regency with a total of 16 deaths out of 10,000 births. The exact cause of pre-eclampsia is still not known for certain, so preeclampsia is called "the disease of theories”. The aim of this research is to determine the description of the risk factors for pre-eclampsia in Tanggamus Regency, Lampung. The research method in this first year used a quantitative research design with a cross sectional approach. The population in this study was pregnant women in Tanggamus district, Lampung. The instruments used in this study were questionnaires and anthropometric examination tools (BMI), data analysis in this study was the Univariate test, Bivariate uses the Chi square test and Multivariate uses the logistic regression test. The results of the research show that there is a relationship between age, parity, BMI, obesity, history of chronic disease, physical activity, nutritional status and attitude towards the incidence of pre-eclampsia with a p-value 0.05, while there is no relationship between the variables education, work, distance. pregnancy, eating patterns, smoking habits, ANC visits, family support, knowledge and economic status with the incidence of pre-eclampsia with a p-value 0.05. And the most dominant variable related to Cervical Cancer is History of Chronic Disease with a p-value of 0.000 and OR: 70.636. Pregnant women should diligently control for early detection so that therapy is given quickly and appropriately to prevent pregnancy complications even during delivery.